Determination of the sediment contamination level in Dangli Waters of Langkawi UNESCO Global Geopark, Kedah, Malaysia - Mazlin Mokhtar,; Jamil Tajam,; Sukarno Wagiman, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Dangli Waters ecosystem is located at the north of Langkawi UNESCO Global Geopark. Apparently, this area is currently experiencing a significant deterioration of marine habitat. Therefore, 14 stations were set up in this study area to investigate the sediment for metal contents discharged into Dangli Waters using the ecological risk assessment. The sediment samples were collected during four seasons, namely South West Monsoon, First Inter Monsoon, North East Monsoon and Second Inter Monsoon. The spatial distribution pattern of heavy metals in sediment was properly determined as well as the seasonal variation of the contamination. From the results obtained, the average concentration of each heavy metal distributed in the surface sediment of Dangli Waters can be written in decreasing order as Fe>Cr>As>Co>Cd. From the observation, heavy metal concentrations of As was recorded the most higher profiles near to the cement plant production area. Meanwhile, for the pattern of seasonal changes, FIM season was defined as the season with higher concentrations of all metals in the surface sediment compared to other seasons. This is due to highly rainfall distribution and water runoff during this period, leading an increase of sediment deposition into the Dangli Waters. According to the contamination factor (Cf) for each metal, it was shown that some heavy metals such as As were at a risky level with the Cf value was higher than 6 (Cf >6). However, the degree of contamination (Cd) for each station was classified as moderate (7 ≤ Cd < 14), except for ST2 which showed a low degree of contamination.